The chromosome-scale reference genome and transcriptome analysis of Solanum torvum provides insights into resistance to root-knot nematodes - Zhang, Hongyuan; Chen, Hao; Tan, Jie; Huang, Shuping; Chen, Xia; Dong, Hongxia; Zhang, Ru; Wang, Yikui; Wang, Benqi; Xiao, Xueqiong; Hong, Zonglie; Zhang, Junhong; et al. (Frontiers in Plant Science, 2023)
Solanum torvum (Swartz) (2n = 24) is a wild Solanaceae plant with high economic value that is used as a rootstock in grafting for Solanaceae plants to improve the resistance to a soil-borne disease caused by root-knot nematodes (RKNs). However, the lack of a high-quality reference genome of S. torvum hinders research on the genetic basis for disease resistance and application in horticulture. Herein, we present a chromosome-level assembly of genomic sequences for S. torvum combining PacBio long reads (HiFi reads), Illumina short reads and Hi-C scaffolding technology. The assembled genome size is ~1.25 Gb with a contig N50 and scaffold N50 of 38.65 Mb and 103.02 Mb, respectively as well as a BUSCO estimate of 98%. GO enrichment and KEGG pathway analysis of the unique S. torvum genes, including NLR and ABC transporters, revealed that they were involved in disease resistance processes. RNA-seq data also confirmed that 48 NLR genes were highly expressed in roots and fibrous roots and that three homologous NLR genes (Sto0288260.1, Sto0201960.1 and Sto0265490.1) in S. torvum were significantly upregulated after RKN infection. Two ABC transporters, ABCB9 and ABCB11 were identified as the hub genes in response to RKN infection. The chromosome-scale reference genome of the S. torvum will provide insights into RKN resistance.